The macroeconomy : a business perspective - Cuthbertson, Keith; Gripaios, Peter (London : Interantional Thomson Business Press, 1997)
Economics
Keywords: Macroeconomy; Macroeconomics; Supply; Inflation; Financial environment; Forecasting; Exchange rates; Economic policy